2021
DOI: 10.3389/fpsyg.2021.687205
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Impact of Social Capital on Entrepreneurship Performance: The Moderation Effects of Opportunity Recognition and Operational Competency

Abstract: Social capital, which is derived from psychological research, has an important value in the construction of network relationships in enterprises. It influences the direction and tendency of network connections in start-up enterprises and has gradually become an important factor in the study of entrepreneurship by scholars. However, the relationship between this and the effectiveness of innovation is unclear. In this study, the social capital is divided into bonding social capital and bridging social capital, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 57 publications
1
19
0
Order By: Relevance
“…Entrepreneurship can be understood as a system or network of interconnected actors closely linked to today's complex social challenges such as sustainability [59]. Social networks promote the growth and development of established and start-up companies by enabling individuals, teams, and organizations to gain access to external information and resources [55]. In a similar vein, De Carolis et al [60] results confirm that the progress of new startups is directly related to social networks and relational capital.…”
Section: Relationship Coordination Capacity (Rcc)mentioning
confidence: 89%
See 1 more Smart Citation
“…Entrepreneurship can be understood as a system or network of interconnected actors closely linked to today's complex social challenges such as sustainability [59]. Social networks promote the growth and development of established and start-up companies by enabling individuals, teams, and organizations to gain access to external information and resources [55]. In a similar vein, De Carolis et al [60] results confirm that the progress of new startups is directly related to social networks and relational capital.…”
Section: Relationship Coordination Capacity (Rcc)mentioning
confidence: 89%
“…Tatikonda et al [54] manifest that those specific operational capabilities support the survival of startups and have a particular influence on specific life stages of startups. In addition, Xie et al [55] research on agricultural entrepreneurs shows that operational capability reflects the entrepreneur's ability to coordinate and manage business projects. Strong operational capabilities will focus on existing network relationships and resources, as well as the integration of management to improve the survival and development of business projects.…”
Section: Operation and Management Capacity (Omc)mentioning
confidence: 99%
“…This research focused on the social capital of entrepreneurs. Bourdieu was the first to define social capital (Xie et al, 2021 ). Social resources are social capital from a functional standpoint.…”
Section: Review Of Literature and Hypotheses Developmentmentioning
confidence: 99%
“…However, there is a lack of study interest on the social capital of entrepreneurs and its impact on entrepreneurial performance or the success in the field of corporate sector management of China. The research conducted by Xie et al ( 2021 ) focused on social capital and its components such as bonding and bridging in relationship to entrepreneurial performance in the agricultural context, leaving a research gap for future researchers to find the impact of other factors along with social capital on entrepreneurial success and performance in other fields as well. Moreover, the research also found moderating roles of operational competency and opportunity recognition toward entrepreneurial performance supporting a moderation of opportunity capacity.…”
Section: Introductionmentioning
confidence: 99%
“…As Waelde et al (2017) pinpointed, through Interpersonal activities, learners are tolerant of opposing viewpoints and have interest-based discussions which also boost their motivation and correspondingly result in their overall fulfillment (Olivero & Oxford, 2019). Several studies proved the relationship between teachers’ interpersonal communication behaviors and students’ engagement, motivation, and success ( Derakhshan, 2021 ; Xie and Derakhshan, 2021 ).…”
Section: Multidimensional Peacementioning
confidence: 99%